2009
DOI: 10.1021/bi9011379
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Autophosphorylation Sites of LRRK2

Abstract: Parkinson's disease (PD) is a major adult-onset neurodegenerative disorder affecting the extrapyramidal motor system. A subset of patients develop PD as an autosomal dominant trait, of which PARK8 caused by mutations in the leucine-rich repeat kinase 2 (LRRK2) gene is highlighted because of its high frequency and clinicopathological similarity to sporadic PD. Previous studies have suggested that overactivation of LRRK2 caused by missense mutations leads to neuronal toxicity in PARK8, although the regulatory me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 24 publications
6
96
0
Order By: Relevance
“…LRRK2 has been found to autophosphorylate > 20 serine and threonine residues in vitro 37, 50, 56, 57, 58, 59, 60, 61. The majority of the autophosphorylation sites reside in the ROC domain, with only a few in the COR and kinase domains (Fig.…”
Section: Importance Of Lrrk2 Autophosphorylation and Constitutive Phomentioning
confidence: 99%
“…LRRK2 has been found to autophosphorylate > 20 serine and threonine residues in vitro 37, 50, 56, 57, 58, 59, 60, 61. The majority of the autophosphorylation sites reside in the ROC domain, with only a few in the COR and kinase domains (Fig.…”
Section: Importance Of Lrrk2 Autophosphorylation and Constitutive Phomentioning
confidence: 99%
“…An analysis of autophosphorylated LRRK2 by matrix assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometery revealed that Ser1403, Thr1404, Thr1410, Thr1491 in the ROC domain, as well as Thr1967 and Thr1969 in the kinase domain, can all be autophosphorylated (60). Kinase assays of LRRK2 using various synthetic peptides showed that the enzyme prefers to phosphorylate Thr over Ser residues, and one study developed a synthetic peptide, Nictide, as a LRRK2 substrate for in vitro kinase assays (61).…”
Section: Molecular Biological Features Of Lrrk2 and Its Pathological mentioning
confidence: 99%
“…Reciprocal regulation of GTP binding by the kinase domain may also occur, as LRRK2 autophosphorylates several residues within the ROC domain. Phosphorylation of T1491 and T1503 residues apparently diminishes GTP binding [24][25][26][27][28][29], suggesting that LRRK2 GTPase may be functionally downstream of the kinase activity [30], although more complex situations may occur. These suggestions show that there is intramolecular communication between different LRRK2 domains, pointing out how complex the molecule is.…”
Section: Introductionmentioning
confidence: 99%